2022
DOI: 10.25122/jml-2021-0287
|View full text |Cite
|
Sign up to set email alerts
|

The status of adolescent health during the COVID-19 pandemic

Abstract: Coronavirus is a life-threatening disease with many devastating psychological, emotional, social, and sexual implications, especially for vulnerable people. This cross-sectional study aimed to assess adolescent health and anxiety during the COVID-19 pandemic. 1300 male adolescents filled out the Male Adolescent Health Need Assessment Scale (MAHNAS) and corona-related anxiety scale (CRAS) from January to May 2021. Data analysis was done using SPSS version 22. The mean age of adolescents was 15.5±2.25, and most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…This is consistent with a Lithuanian study from 2022, where more than half (58%) of the 11-19-year olds reported good well-being and 18.8% reported a risk for depression [41]. It should be noted that in the 2018 HBSC study in Slovenia, 65.0% of the adolescents (11,13,15, and 17 years old) reported good well-being and 13.4% reported depression risk [52].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is consistent with a Lithuanian study from 2022, where more than half (58%) of the 11-19-year olds reported good well-being and 18.8% reported a risk for depression [41]. It should be noted that in the 2018 HBSC study in Slovenia, 65.0% of the adolescents (11,13,15, and 17 years old) reported good well-being and 13.4% reported depression risk [52].…”
Section: Discussionsupporting
confidence: 88%
“…Adolescents who lack access to reliable technology, high-speed Internet, and digital literacy are at a disadvantage compared to their better-off peers [ 8 , 10 , 11 , 12 , 13 , 14 ]. In addition, the pandemic caused economic hardship for many families, which may disproportionately affect adolescents’ health [ 15 ], mental well-being [ 6 , 16 , 17 ], relationships [ 18 ], and health behaviours [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the domain of reproductive health, the pandemic's mental toll on the global population, especially adolescents, has been undeniable [16,17]. Factors such as isolation, uncertainties about the future, and the challenge of adapting to new modes of learning have potential implications on anxiety and depression levels [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…As of March 2020, in-person education was suspended for over a year because of the COVID-19 pandemic in South Korea ( 12 , 13 ). Adolescents began to spend most of their time studying and performing daily activities at home.…”
Section: Introductionmentioning
confidence: 99%